Examen de auditoría integral a la Dirección Zonal del Área de Administración Escolar de la Coordinación de Educación Zona 4, en el período de 1 de Enero al 31 de Diciembre del 2012. - Menéndez Barrezueta, Marilú Elizabeth (2014)
The development of this research was the main purpose of a review of comprehensive audit to Zonal Directorate of the Department of School Administration Coordination of Education Zone 4 study was based on executing all phases of comprehensive audit oriented area review the reasonableness of the balances related internal control system, compliance with the main laws and business management to address Zonal Area School Management Education Coordination Zone 4; to generate the report comprehensive review and corrective actions; proceeding to investigate sufficient literature to lend credibility and support to the theoretical framework, continuing with the presentation of the conclusions and recommendations finally show hypothesis is presented, so it is feasible to do so, since there were no operational or functional impairment that avoid making a financial audit in this entity rather highly positive results were noted, allowing the generation of recommendations, providing improvement actions for the Bank